Cultural Aspects of Type-2 Diabetes-related Social Stigma: A Cultural Epidemiological Study among General Community Members in Urban Pune, India - Abhay Machindra Kudale; Mayuri Dnyandeo Ghawat; Akshada Vikram Gopale; Mugdha Sharad Phutane; Saju Joseph (Indian Journal of Community Medicine)
There is growing evidence from developed countries that type 2 diabetes stigma has been prevalent. However, whether or not type 2 diabetes has a social stigma in India has not been explored. Against this background, a study was attempted to clarify type-2 diabetes-related stigma among general community members. A cross-sectional community-based survey using a locally adapted Explanatory Module Interview Catalog was conducted among 100 randomly selected general community members who did not have diabetes from slum pockets of Pune city. The stigma index was computed based on the responses of stigma indicators and the internal consistency assessed. In addition, based on the mean prominence values, socio-cultural group characteristics were analyzed across stigma indicators. Further, multivariate logistic regression assessed the relationship between socio-demographic characteristics as predictors and stigma indicators as outcome variables. General community members reported widespread awareness regarding type-2 diabetes. More than half of the respondents perceived that diabetes would be a fatal disease without any outside treatment. The resultant stigma index was 7.22 (Cronbach’s alpha = 0.75). The milder stigma for type-2 diabetes was revealed through the preference to hide, problems in arranging marriages, difficulties in ongoing marriages, and discrimination instances at the workplace. Adjusted logistic regression (AOR) across stigma indicators showed a tendency to hide diabetes across marital status (AOR = 8.39) and difficulty forming marriage alliances across religions (AOR = 3.10). Documented socio-cultural features of stigma should be considered priorities for action to mitigate its negative influence on the physical health and emotional well-being of persons who have diabetes.